Do People Judge Sexual Harassment Differently Based on the Type of Job a Victim Has? - Carolyne Georgiana Halfon; Destiny McCray; Danica Kulibert (Behavioral Sciences)
Victims of sexual harassment report facing barriers and retaliation for reporting their sexual harassment. The current study assessed one potential reason for these issues: perceptions of sexual harassment events. Participants (N = 427) read about different sexual harassment events and were told that the woman in the event worked with a masculine (e.g., EMT, school police officer, plumber) or feminine job (e.g., nurse, teacher, cleaning staff). Across three different sexual harassment claims (e.g., unwanted romantic attention, physical groping, being shown sexually explicit images), participants reported that women in masculine jobs were less prototypical women than women in feminine jobs. Furthermore, these perceptions of prototypicality impacted how participants viewed the victim’s sexual harassment event. The less a person views a victim as a typical woman, the less likely they are to label the victim’s experience as sexual harassment. The results suggest that perceptions of sexual harassment are directly impacted by how people view a victim. Implications around prototypes of women and sexual harassment claims are discussed.